ANALYSIS OF WATER QUALITY AND CAPACITY OF THE PEGIRIAN RIVER, SURABAYA USING THE QUAL2KW METHOD - Fissuroyya, Verina Himmatuha; Setyowati, Rr Diah Nugraheni; Nengse, Sulistiya; Hakim, Abdul (Fakultas Teknik Universitas Khairun, 2025)
Pegirian River is a tributary of the Kalimas River from Undaan street which empties into the Tambak Wedi sluice gate. The results of the BLH Surabaya laboratory analysis in 2015 showed that the BOD concentration in the Pegirian River throughout the year did not meet quality standards. This study intends to evaluate water quality based on physical, chemical and biological parameters applying the Qual2Kw model; to assess water quality status by applying data from STORET; and to determine the capacity of the Pegirian River. Samples were taken from four locations in the morning and evening with the parameters tested being temperature, TSS, pH, BOD, COD, DO, PO4, NH3, and E coli. Based on modeling with Qual2Kw, the quality of the Pegirian River in simulation 1 (existing) shows that the BOD, phosphate, amonia and E coli parameters have exceeded class IV river quality standards, thus indicating that the quality of the Pegirian River is polluted. For simulation 2 (prediction for 2029) only the BOD parameter exceeds class IV river quality standards. Simulations 3 (self purification) and 4 (capacity capacity) are still in line with class IV river quality standards for all parameters. The water quality status of the Pegirian River according to the STORET method obtained a total score of -47.75 which indicates a heavily polluted status. Pegirian River has a capacity for TSS, BOD, COD, phosphate, amonia and E coli parameters.